2022
DOI: 10.1177/09564624221138351
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy in the treatment of condyloma acuminata: A systematic review of clinical trials

Abstract: Introduction Condylomata acuminata (CA) is a sexually transmitted infection with a high prevalence associated with psychosexual morbidity in both men and women of various age. Up to now, treatment modalities yield low clearance and recurrence rate (RR) and are also deemed low quality evidence-wise. Photodynamic therapy (PDT) is a novel and promising therapy to effectively cure and prevent CA recurrence. Method This systematic review was reported according to the Preferred Reporting Items for Systematic Review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…BP and BD disease are generally accompanied by keratinocytes with dysmorphic nuclear division, while CA is not. 7,19,20 Studies have found that BP and BD are mainly caused by high-risk HPVs, especially HPV16 and HPV18, and the malignant-related HPV E6 oncogene mainly acts on the catalytic subunit of human telomerase reverse transcriptase (hTERT), which activates the enzyme transcription and increases the telomerase activity of cells, leading to the process of tumour formation. 21 Other risk factors, such as smoking, 22 homosexual, 23,24 herpes simplex virus (HSV) 25 and human immunodeficiency virus (HIV) 26,27 infection, and use of immunosupresive drugs, 13,14,28 were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BP and BD disease are generally accompanied by keratinocytes with dysmorphic nuclear division, while CA is not. 7,19,20 Studies have found that BP and BD are mainly caused by high-risk HPVs, especially HPV16 and HPV18, and the malignant-related HPV E6 oncogene mainly acts on the catalytic subunit of human telomerase reverse transcriptase (hTERT), which activates the enzyme transcription and increases the telomerase activity of cells, leading to the process of tumour formation. 21 Other risk factors, such as smoking, 22 homosexual, 23,24 herpes simplex virus (HSV) 25 and human immunodeficiency virus (HIV) 26,27 infection, and use of immunosupresive drugs, 13,14,28 were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bowenoid papulosis, BD and condyloma acuminata (CA) are disease that with similar phenotypic change and are all closely related to HPV infection, but the histopathological manifestations are different. BP and BD disease are generally accompanied by keratinocytes with dysmorphic nuclear division, while CA is not 7,19,20 . Studies have found that BP and BD are mainly caused by high‐risk HPVs, especially HPV16 and HPV18, and the malignant‐related HPV E6 oncogene mainly acts on the catalytic subunit of human telomerase reverse transcriptase (hTERT), which activates the enzyme transcription and increases the telomerase activity of cells, leading to the process of tumour formation 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This therapy appears to have a higher efficacy with a lower risk of recurrence compared to CO2 laser. [19] Side effects are minimal. Furthermore, photodynamic therapy is a simple procedure and can be used as an element of the combined treatment of condyloma acumina, reports specify the combination of PDT with laser therapy as a highly effective method.. [20] DIFFERENTIAL DIAGNOSIS Condyloma acuminata should be differentiated with a number of diseases, e.g: condyloma lata, lichen planus, psoriasis, pearly penile papules, sebaceous cyst and more.…”
Section: New Methodsmentioning
confidence: 99%
“…Activation of this compound occurs through exposure to light at a specific wavelength, leading to the generation of singlet oxygen and subsequent cellular demise. 4,5 Notably, 5-ALA PDT has demonstrated efficacy in treating condyloma acuminatum 6 and has exhibited curative potential even in cases of HSIL. 7 5-ALA can be applied directly to the lesion inside the endocervical canal, and followed by phototherapy with inserted luminescent laser fiber.…”
Section: Introductionmentioning
confidence: 99%